DEVELOPMENT OF BUSINESS TOURISM IN THE SAMARKAND REGION - Musayeva Shoira Azimovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article discusses the uniqueness of business tourism, the tourism business, the path to new opportunities and prospects for tourism, tourism and hotel organizations focusing on other market segments, business visits based on guest information.